Inclusion Body Myositis - Dimachkie, Mazen M.; Barohn, Richard J. (Seminars in Neurology, 2012)
The idiopathic inflammatory myopathies are a group of rare disorders that share many similarities. These include dermatomyositis (DM), polymyositis (PM), necrotizing myopathy (NM), and sporadic inclusion body myositis (IBM). Inclusion body myositis is the most common idiopathic inflammatory myopathy after age 50 and it presents with chronic proximal leg and distal arm asymmetric mucle weakness. Despite similarities with PM, it is likely that IBM is primarily a degenerative disorder rather than an inflammatory muscle disease. Inclusion body myositis is associated with a modest degree of creatine kinase (CK) elevation and an abnormal electromyogram demonstrating an irritative myopathy with some chronicity. The muscle histopathology demonstrates inflammatory exudates surrounding and invading nonnecrotic muscle fibers often times accompanied by rimmed vacuoles. In this chapter, we review sporadic IBM. We also examine past, essentially negative, clinical trials in IBM and review ongoing clinical trials. For further details on DM, PM, and NM, the reader is referred to the idiopathic inflammatory myopathies chapter.
Keywords: inclusion body myositis; idiopathic inflammatory myopathies; polymyositis; pathophysiology; therapy; prognosis